Development of a biopsychosocial-spiritual model of coping in Muslim parents of Person with Autism (PWA) / Siti Patonah Mohamad - Siti Patonah , Mohamad (2022)
Autism Spectrum Disorder (ASD) is a neurodevelopmental disorder with dysfunctions of certain nervous system parts. The lifelong condition of a person with autism (PWA) is characterized by complex disabilities, presented as impairments in social communication and/or interaction, and behavioural rigidity. Caring and raising PWA with these symptoms throughout his/her lifespan is challenging. Thus, the well-being maintenance of parents of PWA is critical in enabling a balanced lifestyle. Past research have examined the various coping strategies by parents of PWA in search of the best method in fostering wellbeing and overcoming challenges faced. Coping strategies are the cognitive and behaviours of an individual in dealing with stress, consciously or unconsciously. A holistic coping, which integrates aspects of biological factors (physical/ physiological), psychological factors (mental/ emotion), social factors (environment) and spiritual factors (soul), would be ideal. Prior to studying the coping strategies used by Muslim parents of PWA, the stress sources were first identified; for example, the expression of the symptoms of autism by the PWAs. This study utilized a mixed-method, sequential, explanatory research design in exploring the complex, dynamic process of coping and its impact on the wellbeing of Muslim parents of PWA. The quantitative phase was conducted including 49 parents (40 mothers and 9 fathers, Mparentage=41.10 years; Mchildage=11.03 years). Descriptive analysis described items from the sociodemographic questions and core scales: (i) Autism Parenting Stress Index (APSI), (ii) WHOQOL-BREF, and (iii) WHOQOL-Spirituality, Religiousness, and Personal Beliefs (SRPB). Slightly more than half of the respondents (51.0%) expressed low levels of parental stresses, while 49.0% respondents showed moderate or high level of stress. More than half of the respondents (53.1%) demonstrated high level for their wellbeing/ quality of life (QoL), while 77.6% of the respondents showed high level of spirituality and religiosity. The results reflected good condition of QoL and spirituality in majority of these parents. Inferential analysis was done by using the IBM SPSS statistics (SPSS) software. Correlation analysis showed low, negative correlation between parental stress and both QoL (rs= -.388, p= .006), and spirituality (rs= -.350, p= .014). However, a moderate, positive correlation was shown between QoL and spirituality (rs= .548, p= .000). Multiple linear regression exhibited by the 8 SRPB facets explained a significant proportion of variance in predicted parenting stress (i.e., Facet S8 Faith: ß =-.692, t=-2.738, p<.05) and QoL (i.e., Facet S6 Inner peace: ß=.327, t=2.159, p<.05). Whereas General Domain of QoL was the only factor influencing parental stress (ß =-.756, t=-3.359, p<.05) and Core Autism Domain predicting the spiritual condition of Muslim parents (ß =-.376, t=-2.130, p<.05). For the qualitative study, parents with higher score in QoL and spirituality were then selected (n=6; 3 mothers and 3 fathers); representing homogeneity of sample population and the real experienced and practices by parents. Thematic analysis shown that spiritual/ religious coping was most applied by the parents, followed by psychological, social, and physiological aspects. The sub-themes analysis was elaborated in the study and biopsychosocial-spiritual coping was proposed for the intervention of Muslim parents of PWA.